PENERAPAN PRINSIP PEMBIAYAAN MURABAHAH PADA KSPPS BMT NUSA UMMAT SEJAHTERA KC. CIREBON TINJAUAN PERSPEKTIF HUKUM ISLAM - Hafni Khairunnisa; fadli abdullah (UIN Siber Syekh Nurjati Cirebon, 2022)
Murabahah is one of the fund distribution products that is quite popular with BMT customers because of its profitable characteristics. However, even though the implementation is easy and much-loved by the public, Murabaha financing also has many problems. Many factors include ordinary people who still do not understand about murabahah financing, because there are still many people who think that murabahah financing is the same as conventional financing. In fact, according to the DSN-MUI fatwa, this is not the case. For this reason, the author aims to conduct an analysis of the application of the principle of Murabaha financing. This research was conducted at KSPPS BMT Nusa Ummat Sejahtera KC. Cirebon, whose address is at Jalan Raya Tengah Tani No. 17 Dawuan Village, Tengah Tani Subdistrict, Cirebon Regency. The focus of the research is on an analysis of the condition of the BMT in the village, both institutional conditions, services, and practices in the field. The subjects of this research are the managers of BMT Nusa Ummat Sejahtera. The research methods used descriptive qualitative. The result of the research is murabahah funding as a one of product Â which BMT NU Sejahtera practically have doing by islamic principle. Â